Enhancement of unsafe behaviors in simulated moped-riding performance under the influence of low dose of alcohol. (March 2020) - Centola, Carmela; Tagliabue, Mariaelena; Spoto, Andrea; Palpacelli, Marco; Giorgetti, Arianna; Giorgetti, Raffaele; Vidotto, Giulio
Highlights: Alcohol is more frequently involved in fatal crashes of motorcyclists than car drivers. In most countries legal BAC limits are the same for motorcyclists and car drivers. We recorded moped-riding simulated behaviors under placebo/alcohol administration conditions. The results show an increase of danger in facing hazards under low doses of alcohol. Conclusions support governmental decisions to set legal BAC limits at low levels. Abstract: The effects of low levels of blood alcohol concentration (BAC) on motorcyclist performance are still not fully comprehended. The great majority of the studies are, in fact, focused on car driving. So far, it is known that even BAC levels below the legal limit negatively affect riding motor skills correlated with crash rate. In the present study, we used a moped riding simulator to investigate the effects of low alcohol dosages (under the limits established in Italy, and in most European countries) on the defensive riding ability of light drinkers, particularly focusing on the degree of danger characterizing their riding performance. We recruited 24 participants through a double-blind, random distribution, balanced, cross-over design. We administered moderate amounts of alcohol to participants during two sessions of moped riding simulation. The results showed that even though BAC levels were always below (mean value: 0.03 g/dL) the limit allowed by Italian traffic law (0.05 g/dL), alcohol induced a reduction in safe riding behaviors, as indicated by the greater amount of hazardous scenes faced with dangerous riding behaviors when participants were under the influence of alcohol than when they were sober. Moreover, low BAC levels had a greater detrimental influence when a certain amount of learning had already been achieved by the participants (i.e., in the last experimental session). The results suggest that the effect of a low dose of alcohol interacts with participants' self-confidence.